Evaluación comparativa sobre la calidad de imagen y sonido de los sistemas TDT, IPTV y OTT en un entorno urbano controlado bajo condiciones homogéneas en la ciudad de Cuenca. - Parada Soria, Marco Gabriel (2026)
This study compares the image and audio quality of three audiovisual delivery systems, specifically Digital Terrestrial Television (DTT–ISDB-Tb), IPTV and OTT, under homogeneous conditions within the urban environment of Cuenca. A mixed methodology was applied based on ITU-R BT.500 and ITU-T P.910 recommendations, integrating technical measurements such as MER, C/N, BER, latency, jitter, packet loss and bitrate with a subjective evaluation using the ACR/MOS method applied to 30 observers. TDT was assessed under ideal reception conditions, whereas IPTV and OTT were examined in real domestic environments. The results reveal clear differences among the systems. TDT demonstrated the highest technical stability and consequently achieved the highest MOS. IPTV obtained strong perceptual quality although with moderate variability, while OTT presented the greatest fluctuation due to resolution changes and buffering events. Overall, the findings suggest that perceived quality is directly influenced by the technical stability of the distribution channel.